VEGETABLE CONSUMER BEHAVIOR IN MARKET AREA OF JEMBER CITY - Kukuh Iswahyudi; Henik Prayuginingsih; Syamsul Hadi; Risa M. Muliasari (Business Review and Case Studies, 2020)
Consumer behavior is needed as information material for traders in order to meet consumer needs. Vegetables have important for comsumers, therefore these commodities have great economic value for the agribusiness sector. The research aims to identify consumer behavior, determine the purchasing decision making process and analyze the factors that influence the buying behavior of vegetables in the Jember Regency area market. Data obtained from 100 respondents using a convenience sampling method and researched with attitude analysis (Ab), subjective norm analysis (SN), analysis of consumer behavior (B ~ BI) and factor analysis. The results of the analysis show that consumer behavior in buying vegetables in the Jember Regency City market area is as follows: (1) in traditional markets, is in neutral behavior, which is influenced by vegetable attributes; (2) In the modern market, it is likely behavior, which is influenced by the attributes of vegetables. Factors that influence consumers in making vegetable purchasing decisions in the Jember Regency region in a row are individual factors (age, education, income and lifestyle), psychological factors (beliefs, motivations and perceptions), social factors (family, close friends and coworkers), price factors (prices according to benefits and more affordable prices), distribution factors (product availability, seller services and location) and cultural factors (consumption habits). Keywords: consumer behavior, factor analysis, market, purchasing decisions